Association of cardiovascular health with MAFLD and mortality in overweight and obese adults and mediation by inflammation and insulin resistance - Wanjia Zhang; Menglong Zou; Junyao Liang; Dexu Zhang; Man zhou; Hui Feng; Chusen Tang; Jie Xiao; Qian Zhou; Weiqing Yang; Xiaoqin Tan; Yin Xu (Scientific Reports)
Abstract MAFLD is highly prevalent among overweight and obese individuals. Recently, the American Heart Association proposed a new measure of cardiovascular health (Life’s Essential 8). This study investigated the relationship between the Life’s Essential 8 (LE8) and MAFLD, all-cause and cardiovascular mortality in these populations, exploring the mediating role of inflammation and insulin resistance. This retrospective study used data from the National Health and Nutrition Examination Survey (NHANES, 2007–2018), including 6,885 overweight and obese individuals. LE8 scores were categorized into low, medium, and high groups. Weighted logistic regression and Cox proportional hazards models assessed the relationships between LE8, MAFLD, and mortality. Mediation analyses explored the roles of inflammation and insulin resistance, and weighted restricted cubic spline (RCS) regression examined potential nonlinear associations. Kaplan-Meier survival analysis evaluated survival rates across LE8 groups, and subgroup analyses assessed interactions with demographic characteristics. Additionally, ROC curves were used to explore the predictive accuracy of various inflammation and insulin resistance biomarkers. In model 3, compared to the low LE8 group, the prevalence of MAFLD in the highest LE8 group was reduced by 89% (OR = 0.11; 95% CI: 0.06, 0.20). HOMA-IR mediated 72.26% of the mediation effect. Various inflammation markers, including CRP, hs-CRP, SII, and SIRI indices, mediated effects ranging from 3 to 12%. Compared to the low LE8 group, the highest LE8 group had a 58% reduction in all-cause mortality and a 90% reduction in cardiovascular mortality. Kaplan-Meier analysis showed that the higher LE8 groups had significantly higher survival rates than the low LE8 group. Inflammatory markers mediated 5-17% of the mediation effects. Restricted cubic spline (RCS) curves revealed a non-linear relationship between LE8 and MAFLD. Age interacted with LE8 in several subgroup analyses. ROC curves showed that HOMA-IR had strong predictive accuracy for MAFLD, while SIRI demonstrated potential advantages in predicting mortality risk. In overweight/obese populations, LE8 scores were negatively associated with the prevalence of MAFLD, and risk of mortality. These findings emphasize the importance of maintaining high levels of LE8 scores for primary prevention in overweight/obese populations.